Aspects of body image perception of preadolescent girls of different ethnic groups in Northeastern Johannesburg, South Africa - Bruk, Lila (Stellenbosch : University of Stellenbosch, 2010)
Thesis (MNutr (Interdisciplinary Health Sciences. Human Nutrition))--University of Stellenbosch, 2010.